Cenografias (re)imaginadas: a visualidade da cena através do desenho de cenografia e figurino - Tereza Bruzzi de Carvalho (2024)
This research aims to investigate set and costume drawings as forms of representation, materialisation and memory of the visuality of the scene, considering them as a resource for (re)imagining it. Based on the work of two scenographers - Décio Noviello (Brazil) and Félida Medina (Mexico) - the aim is to understand the role and importance of traces in the practice of scenographers and costume designers who usually focus on the spectacle (the theatrical act) and not on the records of it. In this context, the most significant remnant are the set and costume drawings, which are perceived as a singular image, capable of surviving the ephemerality of the scene and as a device able of constructing a visual spatiality of the scene, with specific characteristics since its origin, which makes it possible to play with time and assume itself as a way of subjectively "feeling" the scene before or after it happens. This work is developed through the creation of scripts by crossing concepts and foundations from the performing and visual arts, architecture, philosophy and psychoanalysis, which allow access, albeit in a fragmented way, to the visuality of the theatre play.